The Limits of Second Amendment Originalism and the Constitutional Case for Gun Control - Lawrence Rosenthal (Washington University Law Review, 2015)
The Supreme Court’s 2008 ruling in District of Columbia v. Heller, 554 U.S. 570 (2008), reshaped decades of Second Amendment precedent and jurisprudence. Using a strictly originalist methodology, the Court in Heller appeared to embrace a largely unqualified right of every person to possess and carry any firearm in common civilian use. Heller seemed to promise the dawn of Second Amendment originalism unencumbered by the nonoriginalist balancing tests and standards of scrutiny common in other areas of constitutional law, but lacking any grounding in the original meaning of the Constitution’s text. Nevertheless, in Heller’s wake, the outlines of a new jurisprudence—one that countenances surprisingly robust regulatory authority and in which originalism plays a surprisingly limited role—are starting to become clear. By considering the Second Amendment jurisprudence emerging in Heller’s wake and Heller’s conclusions about the original meaning of the Second Amendment, this Article assesses whether they have produced—or even are capable of producing—an authentically originalist Second Amendment jurisprudence. This Article seeks to explicate and defend this emerging jurisprudence in terms of the relationship between the Second Amendment’s preamble and its operative clause. It explores, as well, the constitutional case for a robust regime of gun control.
Keywords: Constitutional Law; Gun control; Gun regulation; Second Amendment; Second amendment jurisprudence; Guns; District of Columbia v. Heller; Heller; Originalism